Hormone Signaling Linked to Silkmoth Sex Pheromone Biosynthesis Involves Ca(2+)/Calmodulin-dependent Protein Kinase II-mediated Phosphorylation of the Insect PAT Family Protein Bombyx mori Lipid Storage Droplet Protein-1 (BmLsd1) - Ohnishi, Atsushi (American Society for Biochemistry and Molecular Biology, 2011)
Species-specific sex pheromones released by female moths to attract conspecific male moths are synthesized de novo in the pheromone gland (PG) via the fatty acid biosynthetic pathway. This pathway is regulated by a neurohormone termed pheromone biosynthesis activating neuropeptide (PBAN), a 33-amino acid peptide that originates in the subesophageal ganglion. In the silkmoth, Bombyx mori, cytoplasmic lipid droplets, which store the sex pheromone (bombykol) precursor fatty acid, accumulate in PG cells. PBAN stimulates lipolysis of the stored lipid droplet triacylglycerols (TAGs) and releases the precursor for final modification. PBAN exerts its physiological function via the PG cell-surface PBAN receptor, a G protein-coupled receptor that belongs to the neuromedin U receptor family. The PBAN receptor-mediated signal is transmitted via a canonical store-operated channel activation pathway utilizing Gq-mediated phospholipase C activation (Hull, J. J., Kajigaya, R., Imai, K., and Matsumoto, S. (2007) Biosci. Biotechnol. Biochem. 71, 1993–2001; Hull, J. J., Lee, J. M., Kajigaya, R., and Matsumoto, S. (2009) J. Biol. Chem. 284, 31200–31213; Hull, J. J., Lee, J. M., and Matsumoto, S. (2010) Insect Mol. Biol. 19, 553–566). Little, however, is known about the molecular components regulating TAG lipolysis in PG cells. In the current study we found that PBAN signaling involves phosphorylation of an insect PAT family protein named B. mori lipid storage droplet protein-1 (BmLsd1) and that BmLsd1 plays an essential role in the TAG lipolysis associated with bombykol production. Unlike mammalian PAT family perilipins, however, BmLsd1 activation is dependent on phosphorylation by B. mori Ca(2+)/calmodulin-dependent protein kinase II rather than protein kinase A.